2012
DOI: 10.1002/bmb.20585
|View full text |Cite
|
Sign up to set email alerts
|

Using graph‐based assessments within socratic tutorials to reveal and refine students' analytical thinking about molecular networks

Abstract: Biological systems, from the molecular to the ecological, involve dynamic interaction networks. To examine student thinking about networks we used graphical responses, since they are easier to evaluate for implied, but unarticulated assumptions. Senior college level molecular biology students were presented with simple molecular level scenarios; surprisingly, most students failed to articulate the basic assumptions needed to generate reasonable graphical representations; their graphs often contradicted their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Recent studies suggest that undergraduates taught in traditional ways fail to achieve mastery of key concepts essential to working scientists (Shi et al. , 2011; Trujillo et al. , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that undergraduates taught in traditional ways fail to achieve mastery of key concepts essential to working scientists (Shi et al. , 2011; Trujillo et al. , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It also enabled us to identify parts of the websites and later the text that were confusing for students. As examples, responses to the section on genetic drift suggested that (at least some) students understood its implications (see Figure 3), while responses to materials on chemical reactions and their rates and student thinking about molecular interaction networks (Trujillo et al ., 2012) and the link between gene and phenotype (Henson et al ., 2012) indicated a need to reframe materials.…”
Section: Process Description and Outcomesmentioning
confidence: 99%
“…A number of subsequent innovations, including social reading systems (the now defunct Highlighter.com and nota bene: http://nb.mit.edu), were introduced, together with formative assignments delivered through the beSocratic system (Bryfczynski et al ., 2012a,b, 2015). As time passed, we gathered student data (see as examples Henson et al ., 2012; Trujillo et al ., 2012) and learned lessons from the development of CLUE. We used this evidence and experience to redesign Biofundamentals, transforming it from a website to a textbook and associated materials.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, students needed to know “how mutations in the DNA sequence of a gene … result in phenotypic change; …the relationship of genes to proteins and phenotypes;… and genes’ influences [on]…functions and behaviors of a living organism” (Wefer and Sheppard 2008, 158–159). Relevant knowledge also involved understanding “interactions among molecules … and functional activities that emerge as causal mechanisms within or between cells;” effects of mutations or variations, and “gene regulation (turning genes on and off at the right time)” (Trujillo et al 2012, 101; Bowling et al 2008). Additionally, relevant to our field study, the New Biology standards stress the need for students to be able to develop and fill out mental models of multi-faceted molecular events and “behaviors in molecular systems including, paradoxical behaviors” (AAAS 2011; NRC 2009).…”
Section: Background Knowledge and Skills For Visual Analyticsmentioning
confidence: 99%